Empowering Students Through Discovery Learning Approach - Milahtul Latifah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Abstract: The learning model must be adjusted to the level and characteristics of the class, the subject matter to be discussed, the availability of learning media, and others. So it is very important to determine the right learning model to be used in a lesson so that the goals or learning outcomes are achieved. The Discovery Learning strategy is a component of a constructivist approach that has a long history in education. The idea of ​​discovery learning arises from the desire to give pleasure to children/students in